More than a Feeling: Reflecting on Identity and the Reality of Practice Through a Library and Academic Development Collaboration. Issue 1 (2nd January 2017) - Francis, Miranda; Wingrove, Dallas
Abstract: This paper reflects on a partnership between a Liaison Librarian and an Academic Developer working in a large tertiary institution. Working as outsiders to the discipline, we examine the synergies between the roles of Academic Developer and Liaison Librarian. In light of the rapidly changing nature of higher education, we examine the implications for our roles within the hierarchical nature of the academy and disciplinary tribalism. In doing so, we consider the ways our partnership enabled us to draw upon tacit knowledge to deepen our understandings of identity and how to negotiate change from the outside. We explore some of the shared issues and challenges we face as we endeavour to implement positive change in a continually evolving and complex environment. Such issues include the role of gender. We apply the concepts of 'outsiderness' and 'unhomeliness' as developed by Manathunga to critically reflect on our practice, and explore the challenges and potential of Academic Development and Library partnerships to enable continuous improvement in teaching and scholarship. Our experiences highlight the importance of collegiate conversations as enablers of critical reflection on practice.